Mechanisms of enzyme-catalyzed reduction of two carcinogenic nitro-aromatics, 3-nitrobenzanthrone and aristolochic acid I: Experimental and theoretical approaches - Stiborová, Marie; Frei, Eva; Schmeiser, Heinz H; Arlt, Volker M; Martínek, Václav (International journal of molecular sciences, 2014)
UNLABELLED: This review summarizes the results found in studies investigating the enzymatic activation of two genotoxic nitro-aromatics, an environmental pollutant and carcinogen 3-nitrobenzanthrone (3-NBA) and a natural plant nephrotoxin and carcinogen aristolochic acid I (AAI), to reactive species forming covalent DNA adducts. Experimental and theoretical approaches determined the reasons why human NAD(P)H: quinone oxidoreductase (NQO1) and cytochromes P450 (CYP) 1A1 and 1A2 have the potential to reductively activate both nitro-aromatics. The results also contributed to the elucidation of the molecular mechanisms of these reactions. The contribution of conjugation enzymes such as N,O-acetyltransferases (NATs) and sulfotransferases (SULTs) to the activation of 3-NBA and AAI was also examined. The results indicated differences in the abilities of 3-NBA and AAI metabolites to be further activated by these conjugation enzymes. The formation of DNA adducts generated by both carcinogens during their reductive activation by the NOQ1 and CYP1A1/2 enzymes was investigated with pure enzymes, enzymes present in subcellular cytosolic and microsomal fractions, selective inhibitors, and animal models (including knock-out and humanized animals). For the theoretical approaches, flexible in silico docking methods as well as ab initio calculations were employed. The results summarized in this review demonstrate that a combination of experimental and theoretical approaches is a useful tool to study the enzyme-mediated reaction mechanisms of 3-NBA and AAI reduction.
Keywords: benz(a)anthraceny; adukty DNA; acetyltransferasy; Biocatalysis; Sulfotransferases; Enzymes; Acetyltransferases; enzymy; Aristolochic Acids; sulfotransferasy; molekulární modely; Models, Molecular; kyseliny aristolochové; NAD(P)H dehydrogenasa (chinon); Animals; Benz(a)Anthracenes; lidé; aromatické hydroxylasy; Humans; DNA Adducts; Aryl Hydrocarbon Hydroxylases; zvířata; biokatalýza; NAD(P)H Dehydrogenase (Quinone)